ANALYSIS ON STUDENTS’ TYPES OF SENTENCES IN COMPOSING CONVERSATION AT SMA FREE METHODIST 2 MEDAN - Resperdiana Purba; Hermina Ursula Ujut; Hernawati Br. Sitompul; Angeline Robert Pandori (ELT (English Language Teaching Prima Journal), 2023)
The study identified and analyzed the types of sentences found in the text and what types of sentences were the dominantly used. Researchers use qualitative descriptive research methods by using analysis documents to obtain the desired results. Researchers collected 88 sentences data. The result showed that first, the types of sentences are declarative, interrogative, imperative and exclamative sentence. Declarative sentence consists of 18 data, interrogative sentence consists of 30 data, imperative sentence consists of 24 data and exclamative sentence consists of 16 data. Second, the data analyzed showed that the interrogative sentence is the most frequency dominant used, while the least frequency dominant is exclamative sentence.